Stok Sumberdaya Ikan Demersal Laut Dalam di Perairan ZEEI Samudera Hindia Sebelah Selatan Jawa - Ali Suman (Fakultas Biologi | Universitas Jenderal Soedirman, 2011)
The objective of this research was to study about species composition, distribution, and stock density of deep sea demersal fish in the southern Java of the Indian Ocean EEZ waters. This research was carried out based on data collected from the survey conducted between September and October 2004 using Baruna Jaya IV research vessel. This study was basically conducted by applying swept area method with stratified random sampling. The result showed that the species composition of deep sea demersal fish in southern of Java waters were consisted of 169 fishes, 31 crustaceans and 20 cephalopods and the catch of deep sea demersal fish was dominated by ashiro (Ophidiidae) about 45 % and hair tail (Trichiurus lepturus) about 22 %. The widest of species distribution of these resources in southern of Java waters was Chlorophtalmus nigromarginatus. The highest abundance of deep sea resources were caught on the depth of 700-1100 m and the lowest on the depth 200-400 m. Stock density of these resources in southern off Java waters was ranged from 794-39863 kg/km².